The Metabolic Syndrome and Its Components in African-American Women: Emerging Trends and Implications - Gaillard, Trudy R. (Frontiers in Endocrinology, 2018)
The Metabolic Syndrome (MetS) is recognized as a predictor of cardiovascular outcomes and type 2 diabetes (T2DM). The MetS is a constellation of clinical and metabolic risk factors that include abdominal obesity, dyslipidemia, glucose intolerance, and hypertension. There are ethnic and racial differences in the prevalence of MetS and its components. In general, African-Americans have lower prevalence of MetS when compared to whites, but suffer disproportionately from higher cardiovascular mortality and T2DM. Specifically, African-American women (AAW) have higher rates of T2DM and cardiovascular mortality despite a more favorable lipid and lipoprotein profile. This is paradoxical. However, there is a general upward trend in the prevalence of MetS in the US. The reasons are debatable, but could be multifactorial, including genetics and environmental factors. Thus, there is a need to understand the increasing trend in the MetS, its components, and the associated outcomes for AAW. Therefore, the purpose of this mini review is to (1) understand the increasing prevalence of MetS and its components in AAW and (2) provide suggestions for future prevention of cardiovascular disease and T2DM in AAW.